The figure of (daytime) talk show presenters as generators of opinion , persuasion and political media focus in Spain - Javier Pérez Sánchez; German Llorca-Abad (Anàlisi: Quaderns de Comunicació i Cultura)
This study examines the role of talk show presenters in Spain as key actors in the generation of public opinion and the mediation of the political sphere. Traditionally, the weight of public opinion on television has fallen on evening news and late-night debate programmes; however, the prolonged political polarization and the permanent ongoing campaign environment have shifted this conversation to daytime entertainment formats, where talk shows deal explicitly with political issues. The research analyzes four television formats and the role of their presenters during the campaign days of the European elections 2024: TardeAR (Tele5), Al Rojo Vivo (La Sexta), Espejo Público (Antena 3) and Todo es Mentira (Cuatro). A critical analysis methodology was used to analyze the content of the thematic approach, persuasive techniques, language and political conflicts dealt with. Likewise, it has been evaluated how the presenters’ interventions influence the construction of the political agenda and the molding of public opinion. The results offer clear conclusions on how the presenters and, by extension, the formats, exert a notable influence on the audience’s political opinion, consolidating their role in the media agenda and underlining the importance of greater ethics and informative transparency. At the same time, it highlights the need for diversity of opinion to foster a pluralistic debate and enrich the current media landscape.